Photoacoustic detecting of brain lymphatic dysfunction in inflammatory models - Meng Wang; Dan Wang; Zhigang Wang; Wenbin Shi; Zhiyang Wang (Journal of Innovative Optical Health Sciences)
The brain lymphatic system plays a crucial role in maintaining homeostasis, clearing metabolic waste, and regulating neuroinflammation. Its dysfunction is strongly linked to neurodegenerative diseases such as Alzheimer’s disease and Parkinson’s disease. In this study, we employed dual-contrast functional photoacoustic microscopy to evaluate the impact of lipopolysaccharide-induced central nervous system inflammation on brain lymphatic function and to explore the protective effects of the P2X7 receptor (P2X7R) antagonist. Our findings demonstrated that lipopolysaccharide intervention led to impaired function of the meningeal lymphatic vessels, which was partially restored by the P2X7R antagonist, whereas its effects on the glymphatic system and cerebral vessels were minimal. This study further supports the feasibility of photoacoustic microscopy for assessing brain lymphatic function and highlights the therapeutic potential of P2X7R antagonism. These findings suggest that P2X7R may serve as a key target for modulating brain-lymphatic interactions, providing an experimental foundation for developing intervention strategies for neuroinflammatory and neurodegenerative diseases.